2020
DOI: 10.1108/jbim-01-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Interlinkages between coopetition and organisational innovation in Europe

Abstract: Purpose The purpose of this paper is to analyse the relationship between coopetition and organisational innovation in EU countries. As coopetition is usually studied from an inter-company perspective, this work looks in detail at the “ad intra” dynamics of the coopeting companies to understand how they adjust their organisation or implement organisational innovation to successfully adopt this original approach. Design/methodology/approach Using data from the Eurostat (CIS2014), this research offers a quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Prior research has identified that coopetition, among other things, is a driver of value creation (Bengtsson et al , 2010; Novais Santos, 2021; Ritala, 2009; Ritala and Hurmelinna-Laukkanen, 2009), and innovation (Bicen et al , 2021; Chen et al , 2021; Navío-Marco et al , 2020; Park et al , 2014; Wu, 2014). The reduction of costs, to keep up with the competition, is a rationale for coopetition (Bengtsson and Kock, 2000; Luo et al , 2007; Morris et al , 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Prior research has identified that coopetition, among other things, is a driver of value creation (Bengtsson et al , 2010; Novais Santos, 2021; Ritala, 2009; Ritala and Hurmelinna-Laukkanen, 2009), and innovation (Bicen et al , 2021; Chen et al , 2021; Navío-Marco et al , 2020; Park et al , 2014; Wu, 2014). The reduction of costs, to keep up with the competition, is a rationale for coopetition (Bengtsson and Kock, 2000; Luo et al , 2007; Morris et al , 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%